Virtual Historic Centers: Digital Representation of Archaeological Heritage - Pavia, Sara (Springer Nature, 2022)
Digitization and virtual representation of archaeology and architectural heritage potentially connects tangible and intangible cultural assets allowing for recording, conserving, and documenting cultural heritage. Process workflow, case study, and design framework are presented for virtual historic centers intended for archiving, storage, and dissemination of heritage knowledge and information. The process commences with remote sensing and data capturing technologies such as terrestrial and aerial laser scanning, Global Positioning System (GPS), and digital photogrammetry. The resultant survey data is enriched with new methods for 3D modelling of historic environments based on heritage geographic information systems (HGIS) and historic building information modelling (HBIM). The enhancement of 3D data with semantic attributes as intelligent virtual representation of historic environments allows multiple user scenarios ranging from engineering conservation to education and knowledge extraction in addition to object visualization. Open access computing systems for large data management and dissemination are now being considered; these are based on game engine platforms and Oracle and PostgreSQL spatial databases, which are used for managing large datasets.
Handbook of Cultural Heritage Analysis Chapter 51
Keywords: Virtual cultural heritage; SFM - Photogrammetry; Laser scanning; Architectural conservation; Building conservation; Historic structures; Digital surveying; HBIM; Historic building information modelling; Digital Engagement; virtual architecture